PENGARUH PERSEPSI KUALITAS PELAYANAN, KUALITAS PRODUK DAN HARGA TERHADAP LOYALITAS PELANGGAN FLEXI DI KOTA SEMARANG DENGAN INTERVENING KEPUASAN PELANGGAN - ., Suhaji; Sunandar, Haris (Jurnal Ilmu Ekonomi ASET, 2010)
Technology development and operator increase as PT Telkom competitors make scope of market and customers fewer in number because of customers inloyalty. In accordance with this background, the research was made to find out the case of Flexi productâs decline. To maintain customers, we need to create our customers loyalty by improving our quality of service, quality of product and price. Improvement of those qualities and price will influence our customers satisfaction. And in the end, it will increase our customers loyalty. Key words : quality of service, quality of product, price, customerâs satisfaction, customerâs loyalty.